Tardigrade - um framework android para desenvolvimento de jogos de cartas ubíquos - Rodrigues, Willian Almeida (2019)
Researches in Ubiquitous Games aim at discovering how computing devices and sensors can be used to promote entertainment. They try to extend game experience beyond the virtual world by extrapolating its boundaries to the player’s physical world. These games inherit traditional challenges of both domains (i.e., game development and ubiquitous systems), such as, device heterogeneity, resource discovery, mmunication, and limitation of available resources. In this master thesis, we propose a model for the development of biquitous card games, called Tardigrade. It seeks to minimize the challenges of implementing this kind of ubiquitous game. Tardigrade supports three card types: identifiable cards; interactive cards; and context-aware cards. An Android framework that follows Tardigrade model was also implemented. It provides components for card recognition and management; game state management; and device discovery and communication. A proof of concept has been implemented by using the framework: the Hyper Try game. This game illustrates how the mobile game framework can be instantiated to create ubiquitous card games. Fourteen volunteers evaluated the HyperTry through PLEXQ methodology (Playful Experience Framework Questionnaire). The evaluation results indicate that the game developed is fun and arouses interest, mainly because of its innovative mechanics. Another experiment evaluation was implemented in order to evaluate the framework’s functionalities. This experiment was conducted with a group of six Android developers who performed four coding activities. Each activity represented the instantiation of a framework module. The results indicate that the framework was well accepted. Although distinct profiles of developers, none of them had great difficulties during the instantiation tasks.